Management of School Facilities and Infrastructure for Optimal Utilization - Desmi Yanti (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to systematically analyze previous research on the management of school facilities and infrastructure in order to identify strategies for optimizing their utilization in supporting educational processes. This study employs a Systematic Literature Review (SLR) approach by reviewing 15 relevant journal articles selected based on relevance, research design, and publication credibility. The data were analyzed using thematic analysis to identify key patterns and findings across studies. The findings reveal that effective management of school facilities and infrastructure involves several key stages, including planning, procurement, utilization, maintenance, and supervision; however, common challenges include limited financial resources, lack of systematic maintenance, and suboptimal utilization of facilities, while leadership and stakeholder involvement play a crucial role in improving management effectiveness. The novelty of this study lies in providing a comprehensive synthesis of existing literature by integrating key management components and identifying common gaps in practice, particularly in maintenance systems and resource optimization. The practical implication suggests that schools need to strengthen needs-based planning, implement structured maintenance systems, enhance supervision, and optimize the use of available resources. This study contributes to the field of educational management by offering a systematic overview of best practices and challenges in managing school facilities and infrastructure, which can serve as a reference for policymakers, school leaders, and future researchers.